Genome-Wide Identification of MATE Gene Family in Potato (Solanum tuberosum L.) and Expression Analysis in Heavy Metal Stress - Huang, Yun; He, Guandi; Tian, Weijun; Li, Dandan; Meng, Lulu; Wu, Danxia; He, Tengbing (Frontiers in Genetics, 2021)
A genome-wide identification and expression analysis of Multidrug and Toxic Compound Extrusion（MATE）gene family in potato was carried out to explore the response of MATE proteins to heavy metal stress. In this study, we identified 64 MATE genes from potato genome, which are located on 12 chromosomes, are divided into I-IV subfamilies based on the phylogenetic analysis. According to their order of appearance on the chromosomes, they were named from StMATE1-64. Subcellular location prediction showed that 98% of them are located on plasma membrane, as transporters. Synteny analysis showed that 5 pairs of collinearity gene pairs belonged to members of subfamily I and subfamily II had 2 pairs indicating that the duplication is of great significance to the evolution of genes in subfamily I and II. Gene exon-intron structures and motifs composition are more similar in the same subfamily. Every StMATE gene contained at least one cis-acting element associated with regulation of hormone transport. The relative expression levels of 8 StMATE genes were significantly up regulated under Cu2+ stress as compared with the non-stress condition(0h). After Cd2+ stress for 24 h, the expression levels of StMATE33,, in leaf tissue, were significantly increased, indicating their crucial role in the process of Cd2+ stress. Additionally, StMATE18/60/40/33/5 were significantly induced by Cu2+ stress, while StMATE59 (II) was significantly induced by Ni2+ stress. Our study initially explores the biological functions of StMATE genes in the regulation of heavy metal stress, further providing a theoretical basis for studying the subsequent molecular mechanisms in detail. Keywords: potato, heavy metals, MATE genes, phylogenetic relationship, expression analysis.